The operation of spark ignition engine on various type of fuels - 363091 Johan Ismail (Kuala Lumpur : Universiti Teknologi Malaysia, 1981)
Thesis (Bachelor of Mechanical Engineering) - Universit Teknologi Malaysia, 1981